Behind the cloud : the untold story of how salesforce.com went from idea to billion-dollar company and revolutionized an industry. - Benioff, Marc, ....-; Adler, Carlye, ....- (San Francisco : Jossey-Bass, 2009)
How did salesforce.com grow from a start-up in a rented apartment into the world's fastest growing software company in less than a decade? For the first time, Marc Benioff, the visionary founder, chairman, and CEO of salesforce.com, tells how he and his team created and used new business, technology, and philanthropic models tailored to this time of extraordinary change. Showing how salesforce.com not only survived the dot-com implosion of 2001, but also went on to define itself as the leader of the cloud computing revolution and spark a 46 billion-dollar industry, Benioff's story will help business leaders and entrepreneurs stand out, innovate better, and grow faster in any economic climate. In Behind the Cloud, Benioff shares the strategies that have inspired employees, turned customers into evangelists, leveraged an ecosystem of partners, and allowed innovation to flourish. Benioff shows how salesforce.com pioneered a simple idea (delivering business applications as a service over the Internet) to change the way all businesses use software applications and, ultimately, change the way the software industry works. With Marc Benioff's candid, unconventional advice and unusual call-out lessons from the Salesforce.com Playbook-including Benioff's proprietary management tool, V2MOM-any business can go against the grain, rapidly change the game, and learn how to achieve lasting success.
Inhoudsopgave : 1. The Start-up Playbook 2. The Marketing Playbook 3. The Events Playbook 4. The Sales Playbook 5. The Technology Playbook 6. The Corporate Philanthropy Playbook 7. The Global Playbook 8. The Finance Playbook 9. The Leadership Playbook
Keywords: Marketing -- Strategieën; Software